Strategi Komunikasi dan Keterlibatan Masyarakat dalam Konservasi Mangrove di Jerowaru, Lombok Timur - Hidayat, Arif (Journal of Community Development and Empowerment, 2025)
The mangrove ecosystem plays a vital role in maintaining coastal environmental balance, serving as a natural barrier against abrasion and as a breeding ground for various marine species. However, in many areas—including Jerowaru Village in East Lombok—mangrove degradation occurs due to environmentally harmful human activities and a lack of public awareness regarding the importance of this ecosystem. This study aims to analyze the environmental communication strategies implemented and the extent of community involvement in mangrove conservation efforts in the region. The research employed a qualitative approach, using data collection techniques such as in-depth interviews, field observations, and document studies. The findings indicate that participatory communication involving community leaders, youth groups, and local institutions is more effective in raising awareness and fostering collective action than top-down approaches. The use of traditional media and community discussion forums also plays a significant role in disseminating information and building long-term commitment to conservation. Active community participation not only accelerates the mangrove rehabilitation process but also strengthens a sense of ownership and collective responsibility toward the environment. Thus, participation-based communication strategies are key to ensuring the sustainability of mangrove conservation programs in Jerowaru Village. These findings offer recommendations for policymakers and environmental practitioners to prioritize collaborative approaches in similar coastal programs elsewhere.